An investigation of the responsiveness by insurance companies to regulations affecting their financial performance: a case of Old Mutual Life Assurance Company Zimbabwe. - Dube, Thandeka S. (Midlands State University, 2017)
The aim of this study was to investigate the responsiveness by insurance companies to regulations affecting their financial performance. More specifically the study sought to investigate the effect of profitability, capital adequacy, return on assets, capital requirements and non- financial factors on the financial performance of insurance entities. Primary data was used in this study, where a census survey was preferred as the population of the study was small. A likert scale questionnaire and interviews were used to gather data relation to OMLAC’s performance. The data was sorted and presented on graphs, tables and pie charts to enable descriptive statistics. The results indicated that regulations improves financial performance of an entity. From the findings the study concluded that return on assets, capital adequacy ratio, minimum capital requirements and non- financial factors through regulations significantly influence financial performance of insurance entities. The study recommends that further research should be done on the effect of regulations on profitability determinants, such as size, age and structure of the organisation.